Genomic variants causing mitochondrial dysfunction are common in hereditary lower motor neuron disease - ÜNVER, OLCAY (WILEY, 2021)
Hereditary lower motor neuron diseases (LMND) other than 5q-spinal muscular atrophy (5q-SMA) can be classified according to affected muscle groups. Proximal and distal forms of non-5q-SMA represent a clinically and genetically heterogeneous spectrum characterized by significant overlaps with axonal forms of Charcot-Marie-Tooth (CMT) disease. A consensus for the best approach to molecular diagnosis needs to be reached, especially in light of continuous novel gene discovery and falling costs of next-generation sequencing (NGS). We performed exome sequencing (ES) in 41 families presenting with non-5q-SMA or axonal CMT, 25 of which had undergone a previous negative neuromuscular disease (NMD) gene panel analysis. The total diagnostic yield of ES was 41%. Diagnostic success in the cohort with a previous NMD-panel analysis was significantly extended by ES, primarily due to novel gene associated-phenotypes and uncharacteristic phenotypic presentations. We recommend early ES for individuals with hereditary LMND presenting uncharacteristic or significantly overlapping features. As mitochondrial dysfunction was the underlying pathomechanism in 47% of the solved individuals, we highlight the sensitivity of the anterior horn cell and peripheral nerve to mitochondrial imbalance as well as the necessity to screen for mitochondrial disorders in individuals presenting predominant lower motor neuron symptoms.
Keywords: axonal CMT; exome sequencing; hereditary neuropathy; lower motor neuron disease; mitochondrial dysfunction; non‐ 5q‐ SMA